A COMPERATIVE STUDY OF MACKEREL TUNA AMPLANG WITH ADDITION OF SEAWEED FLOUR (Eucheuma cottonii) - Weni Kurnia Sari; N Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTSeaweed flour has a high dietary fiber content which is good for food production. This study aims to determine the differences in levels of fish amplang (mackerel tuna) fiber added and without addition to seaweed flour. The research method was carried out experimentally by comparing the fish amplang with the addition of 1% seaweed and without the addition of seaweed flour. The results showed that the addition of seaweed flour gave a significant difference to the value of fish amplang fiber. The fiber content of fish amplang with the addition of seaweed flour reached 5.79% and without the addition of seaweed, flour was 2.64%.Keywords: seaweed flour, Eucheuma cottonii, mackerel tuna, fish amplang